Estudo do processo construtivo no sistema light steel framing em cidades do estado do Paraná - Cavichioli, Carla Patricia (2024)
Civil construction in Brazil generates high levels of waste of resources, which requires the use of new methods that promote sustainability. In this sense, Light Steel Framing presents significant advantages such as reducing material waste, execution time and optimization of steps. However, for a good implementation of this system, knowledge about construction practices is required. Therefore, this study aimed to present the main characteristics of the Light Steel Framing construction system and synthesize the information through technical visits. To carry out this work, technical visits were carried out at works of this construction system in the municipalities of Campo Mourão, Maringá, Toledo and Guarapuava in Paraná. The relevant information in these constructions was synthesized using a checklist, texts and figures. The work provided relevant information on the topic, such as understanding the processes, materials and construction details. Furthermore, the technical visits provided a practical and applicable view through interaction with professionals and visualization of the construction technique. Therefore, promoting studies on Light Steel Framing contributes to the preparation to better practice the profession and the implementation of this construction system in the market.